A história no ensino básico em Portugal no último quartel: perspectiva curricular - Correia, Luís Grosso (2015)
The third cycle of basic education (7th 9th year) in Portugal isdiscussed, with reference to the History curriculum. The epistemological,anthropological and societal bases in the curriculum are investigated toconstruct a historical awareness on modernity. The analysis comprises legaland institutional documents that informed the Portuguese curriculum ingeneral and the program of History in particular to deal with the mission andintelligibility of the discipline with the co-relationship of forces between thedifferent areas of knowledge within the third cycle of basic education. Thecurriculum solutions implemented from the 1980s are investigated.